Freeing Grace - Norman, Charity (Crows Nest, NSW : Allen and Unwin, 2022)
Warm, insightful and poignant, Freeing Grace tells the story of David, curate of an inner-city parish, and Leila, his Nigerian-born wife. Unable to have children of their own, they're desperate for a family. When they finally hear they've been approved to adopt a baby, Grace, they can scarcely believe their good fortune. There's just one problem for which David and Leila cannot plan; Grace's birth family - the enigmatic, charismatic Harrisons. Enlisting their friend, the feckless, charming New Zealander, Jake Kelly - who's half in love with all of them, one way or another - the Harrisons send him on a quest that will force a shocking confrontation. Everyone only wants what's best for Grace - but who can say exactly what that is?
Originally published: 2010.
Includes an excerpt from Remember me, by Charity Norman.
"Would you risk everything for your heart's desire?"--Cover.
Keywords: Adopted children -- Fiction; Married people -- New Zealand -- Fiction; Families -- New Zealand -- Fiction; New Zealand -- Social conditions -- Fiction; Domestic fiction